Red country - Abercrombie, Joe (Orbit, 2012)
With her cowardly step father for company, Shy South journeys into the lawless Far Country, reckoning with the Ghosts and being forced into an alliance with the infamous soldier of fortune Nicomo Cosca, with one purpose in mind: to get her family back.